Children's work at Family Agriculture: exploration or learning? (Research, Society and Development, 2020)
This study discuss the relationship between labor and education in the Amazonian basin taking into account the child labor exploitation. The Amazonian scope was invetigatesd, discussing child's right to be a child and the theoretical-procedural fundaments that support rural education. The research is part of the Field Improvement Course into Earth’s School Program and uses participative observation, questionnaires to trace student's profile and a research project to identify local realities in wich children and family work altogether. Thus, we affirm that the work carried out in family agriculture is not child labor exploitation, but a socializiation and learning process, a moment to pass on traditional knowledge to children and young people. Among the difficulties found during Rural Education application and improvement in Amazonas state, we highlight: the fragility of social movements in the State, teacher's turnover due to contracting process, nucleation and the introjection of urban values in the rural context. These problems can be deal with the organization of the people living in the forest, the floodplain and the rivers, rescuing the work-education relationship as the main factor in coping with adversity.